Comparison of the pharmacokinetic profiles of 13 phenolic acids and 6 triterpenes in normal and leukopenia rats after oral administration of Sanguisorba officinalis L. extract by LC‐MS/MS. Issue 22 (14th October 2020) - Fan, Linzi; Wang, Xiaotong; Huang, Jing; Gan, Chunli; Jiang, Shuang; Yang, Xinrong; Yang, Chunjuan; Yao, Meicun
Abstract: A selective, accurate, and efficient liquid chromatography‐tandem mass spectrometry method was developed for the simultaneous determination of 13 phenolic acids. Additionally, for more comprehensively determining the chemical constituents in Sanguisorba officinalis L. extract, a previously developed method was employed for the simultaneous determination of six triterpenes. Thus, two methods were used to ensure the comprehensiveness and reliability of this study. Based on these methods, the pharmacokinetic profiles of the 13 phenolic acids and 6 triterpenes in normal and leukopenia rats after oral administration of S. officinalis L. extract were compared for the first time in the present study. Quantitative detection of the 13 phenolic acids and 6 triterpenes was performed using the multiple reaction monitoring mode with the electrospray ion source in negative and positive electrospray ionization, respectively. Chromatographic separation was performed on an Agilent Eclipse Plus C18 RRHD column (50 × 2.1 mm, 1.8 µm) using gradient elution with a mobile phase composed of methanol–0.1% aqueous formic acid. The pharmacokinetic results demonstrated that the pharmacokinetic characteristics of the 19 analytes in leukopenia rats differed significantly from those determined in normal rats, which could provide a helpful reference for the clinical application of S. officinalis L. in the prevention and treatment of leucopenia.